Libraries' effort to attract user / Siti Aishah Yahpar and Nursyafiqah Wahid - Yahpar, Siti Aishah; Wahid, Nursyafiqah (Faculty of Information Management, 2015)
Purpose- The purpose of this paper is to identify effort that being done by the library in order to attract the user to come to the library. Design/methodology/approach- To provide a context for this work, the paper begins with the article review from some articles based on the library management field as a guideline to write this paper. The result gives more information in order to complete this paper. Findings- The paper proposes many efforts from the library, especially in the service system. It analyzes the functions of organizations and librarians, information resources, services and methods and the interactions between them. Originality/value-The paper discusses the effort of the library to attract user by offering variety of services and methods to share information in order to achieve the library's goals and objectives.